A study on factor influences employee turnover toward SKALI WEB SERVICES / Mohd Hidzir Mohd Hairani - Mohd Hairani, Mohd Hidzir (Faculty of Business and Management, 2010)
Turn over one of the problem that occur in organization which affect not only the employees performance, but also the performance of the organization itself in term of productivity, production as well as services. The main objective of this research is to determine the factors that contribute to employee turnover at the SKALI WEB SERVICES. Besides, researcher also identifies the main factors which affect employee turnover plus the relationship between the factors towards employee turnover. The factors are job/employee satisfaction, organization performance and job related/stress. Researcher used questionnaire as a main instrumental in data collection method. Next, data that have been collected, will be analyzed through frequency, percentage, mean and Pearson Correlation. In general, the results of this research show that factor Job/employee satisfaction is the most influence toward employee turnover. This followed by the factors of organization performance and job related/stress.